DRYING KINETICS MODELLING OF TARAP (ARTOCARPUS ODORATISSIMUS) - Heng Jin Tham; Jau Shya Lee (International Journal of Science and Engineering)
The effects of temperatures, 50˚C, 60˚C and 70˚C on the drying behaviour of tarap slices were experimentally investigated. High drying temperature resulted in shorter drying time and higher drying rate. Results show that the drying of tarap slices occurred at falling rate period. The effective moisture diffusivity increases from 1.216 to 2.432 × 10-11 m2/s with the increase in drying temperature. The activation energy of tarap is found to be 32 kJ/mol and the constant diffusivity is 1.969 × 10-6 m2/s. As for the modelling of drying kinetics, three statistical parameters namely coefficient of determination, reduced chi-square and root means square error were determined, and Midilli-Kucuk model was found to be the most suitable for describing the drying curves of tarap slices.